Cyclic changes in the umbilical arterial flow in mono-chorionic, di-amniotic twin pregnancy - Nakai, Yuichiro; Ishiko, Osamu; Nishio, Junko; Suzuki, Shin-ichiro; Mine, Makiko; Imanaka, Motoharu; Ogita, Sachio (European Journal of Obstetrics & Gynecology and Reproductive Biology, 2002)
Objective: To determine the effect of arterio-arterial anastomosis on the umbilical arterial flow in mono-chorionic, di-amniotic twin pregnancy. Subjects: Thirty-three women with mono-chorionic, di-amniotic twin pregnancy. Methods: Pulsed Doppler ultrasonographic examination was performed every 4 weeks to obtain umbilical arterial flow velocity waveforms in both two fetuses. Results: In five of the women, cyclic flow changes in the umbilical arterial flow were detected in the smaller fetus. All of these twins had arterio-arterial anastomosis on the surface of the placenta. Conclusion: The fetuses in mono-chorionic and di-amniotic twin gestation who showed cyclic changes in umbilical arterial flow had arterio-arterial anastomosis. But, this characteristic flow was not observed every time.